Die literarische Zensur in Österreich von 1751 bis 1848 - Bachleitner, Norbert (Böhlau, 2017)
The impact of censorship on the political and intellectual climate in Austria between 1751 and 1848 can hardly be over-estimated. The book covers the institutions involved in censorship, its procedures and results represented by the lists of banned books, and the censors, authors, publishers, and book-sellers affected by bans. Ten case studies deal with selected literary genres and epochs, the appendix contains documents regarding censorship legislation and administration.